IMF Staff Papers, Volume 48, No. 1 - Flood, Robert (IMF Staff Papers; IMF Staff Papers ;, 2001)
This paper re-examines the issue of the existence of threshold effects in the relationship between inflation and growth, using new econometric techniques that provide appropriate procedures for estimation and inference. The threshold level of inflation above which inflation significantly slows growth is estimated at 1-3 percent for industrial countries and 11-12 percent for developing countries. The negative and significant relationship between inflation and growth, for inflation rates above the threshold level, is quite robust with respect to the estimation method, perturbations in the location of the threshold level, the exclusion of high-inflation observations, data frequency, and alternative specifications.